Valve-Sparing Aortic Root Reimplantation: Early- and Mid-Term Outcomes - Chen, Joshua R.; Shah, Vishal N.; Koeneman, Scott H.; King, Colin; McGee, Jacqueline; Plestis, Konstadinos (AORTA, 2025)
Valve-sparing root replacement (VSRR) is an alternative to traditional valve-replacing root replacement. We examined early- and mid-term outcomes after VSRR.We performed a retrospective review of a prospectively maintained aortic registry. All patients undergoing VSRR from 2005 to 2023 were included. Statistical analysis was performed in R version 4.3.1. Kaplan–Meier curves were used to describe mortality and freedom from mortality, aortic insufficiency (AI) > 1 + , and aortic valve-related reoperation.Eighty-one patients underwent VSRR, 59 (72.8%) through full sternotomy (FS) and 22 (27.2%) through upper hemisternotomy. There were no cases of AI > 1+ in the perioperative period, 1 (1.2%) stroke, and no in-hospital mortality. Mean intensive care unit and hospital stay were 3 and 7 days, respectively. Mean follow-up time was 8 years. Freedom from all-cause mortality at 1, 5, and 10 years was 100, 96.6, and 94.4%, respectively. Composite freedom from reoperation, recurrence, or mortality at 1, 5, and 10 years was 98.8, 92.1, and 87.3%, respectively.With careful preoperative selection, VSRR is a durable procedure for patients with aortic root aneurysm.
Keywords: valve-sparing root reimplantation; David procedure; root aneurysm; upper; hemisternotomy